AUTHENTIC ASSESSMENT OF SPEAKING SKILL FOR GRADE I JUNIOR HIGH SCHOOL - Sahyoni Sahyoni; M Zaim (Fakultas Bahasa dan Seni UNP, 2017)
PENILAIAN OTENTIK KETERAMPILAN BERBICARA UNTUK KELAS I SEKOLAH LANJUTAN TINGKAT PERTAMAAbstractAuthentic assessment plays an important role in the process of learning evaluation. It covers three domains namely affective, psychomotor, and cognitive domains. To assess students’ speaking skill, teachers must apply appropriate authentic assessment to the students. This paper presents the result of a study on developing authentic assessment of speaking skill of English at grade 1 MTsN Batusangkar. Data were obtained through questionnaire, interview, validation checklist and practicality checklist. There were 32 students as the respondents. This paper revealed that there are six authentic assessment models appropriate for grade 1 Junior High School, they are role play, information gap, picture talks, brief question and answer, narrating sequences, and pair dialogue. It is suggested that teachers may apply the six authentic assessment models in assessing students’ speaking skill at grade 1 Junior High School. Key Words: authentic assessment, development model, speaking skill, junior high school.AbstrakPenilaian otentik memainkan peran penting dalam proses evaluasi pembelajaran. Penilaian otentik mencakup tiga domain yaitu: domain afektif, psikomotor, dan kognitif. Untuk menilai kemampuan berbicara siswa, guru harus menerapkan penilaian otentik yang sesuai dengan siswa. Artikel ini menyajikan hasil penelitian tentang pengembangan penilaian otentik untuk keterampilan berbicara di kelas I MTsN Batusangkar. Data diperoleh melalui kuesioner, wawancara, ceklis validasi dan ceklis kepraktisan. Ada 32 siswa sebagai responden. Makalah ini mengungkapkan bahwa ada enam model penilaian otentik yaitu role play, information gap, picture talks, pertanyaan singkat dan jawaban, narasi urutan dan dialog pasangan. Hal ini sangat disarankan bagi para guru untuk menerapkan enam model penilaian otentik dalam menilai kemampuan berbicara siswa.